Emergency Presentations to Child and Adolescent Psychiatry: Nonsuicidal Self-Injury and Suicidality - Franzen, Monika; Keller, Ferdinand; Brown, Rebecca C.; Plener, Paul L. (Frontiers in Psychiatry, 2020)
Nonsuicidal Self-Injury (NSSI) and suicidality are common reasons for emergency presentations in child and adolescent psychiatry. Therefore, we focused on reasons for emergency presentations as well as specific characteristics of those presenting with NSSI or suicidality to an emergeny psychiatric service. We analyzed data from a German university hospital regarding emergency presentations during a 78 months period. NSSI and suicidality were rated according to the Columbia Classification Algorithm of Suicide Assessment (C-CASA). Data from 546 emergency presentations was recorded, of which 347 (63.5%) presented for NSSI or suicidality. Given the high percentage, thorough assessment of sucidality as well as providing adequate treatment in emergency settings to establish further care, is of utmost importance.